Strategi Pengembangan Objek Wisata Taman Bambu Mandira Untuk Meningkatkan Perekonomian Masyarakat - Fransiskus Roy; Vinsenco R. Serano (Universitas Musamus, Merauke, Papua, 2019)
Atractions in a place where we can find continuity and harmony with the environment. The porpuse of this study is to describe how the Departement of Tourism’s strategy in developing Mandira Bamboo Park attractions to inprove the community’s economy. The research method used is a descriptive qualitative technique to explain how the impact of the of the development of the Mandira Bamboo park for the economi of the community. Based on the results of the study that the strategy of the department of tourism in developing the Bamboo Park Mandira tourism object is currently not running optimally because this attractions is newly formed and is also an individual property so that government intervention is very limited or not fully accommodate by the government. Mandira Bamboo Park has emprowered the Tanah Miring community, such as giving an opportunity to the community to open a business increasing its economy, although the impact of attractions in boosting the economi has not been felt by the community as a whole, but processors remain optimistic to develop these atractions.